THE EFFECT OF REWARD BOARD-ASSISTED COURSE REVIEW HORAY (CRH) MODEL ON STUDENTS’ LEARNING OUTCOMES AT GRADE II ELEMENTARY SCHOOLS - Rahmawatin Khasanah; Haris Supratno; M. Bambang Edi Siswanto (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
This study aimed to encourage students to learn by using reward board-assisted CRH model in order to measure the students’ learning outcomes at grade II elementary school. This study applied course review horay (CRH) model assisted by reward board media on Theme 6: “Merawat Hewan dan Tumbuhan” at SDN Jatirejo. The study was an experimental method with Pre-Experimental Design in the form of Intact-Group Comparison. The subjects were students at grade II SDN Jatirejo in academic year 2019/2020. Data were collected through observations and written tests to measure students’ learning outcomes before and after the treatment. Then, the data were analyzed by using t-test formula in order to determine the effect of the treatment in the experimental and control groups. The results revealed that reward board-assisted course review horay model were more attractive and students actively participated in learning so that the teacher could easily deliver teaching materials. It was found that the average score of the experimental group was 11.843 with a very good category  while the average score of the control group was 11,655. This indicated that reward board- assisted course review horay model significantly influenced on the students’ learning outcomes in the experimental group compared to the conventional learning model implemented in the control group. The results of this study was expected to give a contribution as a source of information input and consideration for institutions related to learning theme 6 grade II elementary school. The conclusion from this research was the influence of reward board-assisted CRH model influenced the students’ learning outcomes at grade II elementary school.